Pengaruh Pembangunan Infrastruktur terhadap Pertumbuhan Ekonomi di Indonesia - Arga, Kharisma Idola (Salam (Islamic Economics Journal), 2022)
Development is carried out to improve the welfare of the community. As a developing country, the Indonesian government focuses on infrastructure development. The Indonesian government places physical infrastructure development as a vital sector in achieving equity and high economic growth. It is hoped that the increase in infrastructure development will be able to increase economic growth in Indonesia. The purpose of writing this article is to determine the impact of infrastructure development on economic growth in Indonesia. The method used to write this article is to review the literature and read various news sources as outlined in descriptive writing and an overview of the impact of infrastructure development on economic growth in Indonesia. The conclusions are 1). The increasing development of infrastructure will increase economic growth in Indonesia. The increase in infrastructure development is reflected in the increase in road indicators which are the dominant indicators, because in recent years the Indonesian government has continued to carry out road construction in Indonesian regions, so that roads have a positive contribution to the increase in Gross Domestic Product (GDP) which is an indicators of economic growth in Indonesia 2). economic growth will be accompanied by an increase in economic equity in Indonesia. Increased economic growth is reflected in the dominant increase in Gross Domestic Product (GDP) and the increase in economic equity is reflected in the increase in per capita income which is the dominant indicator. Keywords: Infrastructure Development and GrowthEconomy